Los sistemas de costos que manejan los productores de Plaza Vida de la Ciudad de Riobamba, período 2023 - Flores Chicaiza, Steve Alejandro (2024)
The main objective of the study was to determine the cost systems used by Plaza Vida producers in Riobamba during 2023. A deductive approach and a non-experimental design were adopted, collecting data through documentary review, interviews and surveys with a population of 26 entrepreneurs. analyzed through census sampling. The results revealed a wide diversity of products, such as yogurt, beer, jewelry and agricultural products, which implies challenges in cost management. Many producers lack access to advanced technological tools, limiting efficiency and precision in their management. External factors, such as fluctuating input prices and seasonal variability, significantly affect cost management and pricing. It was concluded that producers need more training to develop efficient and transparent cost systems, and that current cost management has deficiencies that negatively impact decision making and profit generation. Furthermore, the need to adequately value organic products in the market is highlighted. It is recommended to improve the accounting recording methodology, invest in training programs in cost and expense management, and adopt strategies to access broader markets that value products with greater added value. This would not only differentiate the products from standard commercial offerings, but also increase sales volume, reduce redundant costs and improve operational efficiency.